DESIGN OF AUTOMATIC COOLING SYSTEM ALUMINIUM MOLDING BY OMRON E5CZ TEMPERATURE CONTROL - Ardi, Syahril; Afianto, Afianto; Wibowo, Agung (Technologic, 2011)
Shock absorber as a part of motorcycle consist of front fork circuit and OCU (Oil Cushion Unit). Outer tube is outside area of front fork circuit that molded by liquid aluminium at gravity casting machine. The molding has continue cooling water flow system that uncontrolled by the operator. Cooling in below point, midle point, and upper on the molding. This condition has cause defect on the product because the cooling systems. Kind of defect for examples: shrinkage, unperfect, and cavity on outer tube surface. As improvement steps, we design a temperature control system with installing two of temperature sensor. In addition, we modify from manual valve system into the automatic valve system. Manual system will be changed to automatic system by using the principle in thermocontrol, i.e using on-off control method. Based on the improvement results, has been got decrease of defect product from 6.6 % into 2.7%.